Fluoride Removal from Water Using Adsorption Method with Different Compounds: A Comprehensive Review - Kumar, Dharmendra; Kumar, Kameshwar (Journal for Research in Applied Sciences and Biotechnology, 2023)
This comprehensive review paper explores the diverse range of compounds employed in the adsorption process for the removal of fluoride from water. The escalating levels of fluoride contamination in drinking water sources pose a significant health threat to communities worldwide. Adsorption is a widely acknowledged and effective method for mitigating this concern, involving various compounds such as activated carbon, metal oxides, and biomaterials. It focuses on the mechanisms, adsorption isotherms, kinetics, and factors affecting the efficiency of fluoride removal using these compounds. We discuss the advantages and limitations of each compound, considering their applicability in different environmental conditions and scale of operation. Furthermore, we scrutinize the regeneration and cost-effectiveness of these materials. This review consolidates the existing knowledge on fluoride removal via adsorption techniques, offering valuable insights for researchers, policymakers, and practitioners involved in water purification. The main objective of this paper is to present a comprehensive, and up-to-date assessment of the subject matter.